Development of frozen guapple puree - Amara, Ma. Victoria T. (1992)
The study aimed to develop frozen guapple puree for utilization in bakery and ice cream products. An optimum process and formulation for puree production was developed in the pilot scale. It was found that slicing the fruits into very small pieces, approximately 0.25 cm3 greatly provided ease in the pulping with a higher puree yield, 56.6%. The use of the pulper and colloid mill was recommended. The most acceptable Bx-acid ratio of the pure sample was 15:0.7. A slight change in the viscosity reading of the sample due to mechanical destruction of the cellular tissues after frozen storage of 5 days was observed. The physico-chemical characteristics did not exhibit any significant difference upon frozen storage up to the 14th day. A freezing rate curve was established for the slow freezing method, products packed in 1/2 pint plastic containers reached the internal equilibrium temperature of -25°C after 6 hours and those packed in 1 pint plastic containers reached this temperature after 8.62 hours. The pasteurization process of 90°C for 60 seconds was adequate to ensure microbial safety after processing. This, coupled with frozen storage for two weeks by slow freezing method with still air, ensured microbial stability of the puree samples packed in polyethylene bags. The puree can be utilized into muffins, ice cream and sherbet with high acceptability